Vaccination strategy for preventing the spread of SARS‐CoV‐2 in the limited supply condition: A mathematical modeling study. Issue 8 (4th May 2022) - Lin, Yi‐Fan; Li, Yuwei; Duan, Qibin; Lei, Hao; Tian, Dechao; Xiao, Shenglan; Jiang, Yawen; Sun, Caijun; Du, Xiangjun; Shu, Yuelong; Zou, Huachun
Abstract: To mitigate SARS‐CoV‐2 transmission, vaccines have been urgently approved. With their limited availability, it is critical to distribute the vaccines reasonably. We simulated the SARS‐CoV‐2 transmission for 365 days over four intervention periods: free transmission, structural mitigation, personal mitigation, and vaccination. Sensitivity analyses were performed to obtain robust results. We further evaluated two proposed vaccination allocations, including one‐dose‐high‐coverage and two‐doses‐low‐coverage, when the supply was low. 33.35% (infection rate, 2.68 in 10 million people) and 40.54% (2.36) of confirmed cases could be avoided as the nonpharmaceutical interventions (NPIs) adherence rate rose from 50% to 70%. As the vaccination coverage reached 60% and 80%, the total infections could be reduced by 32.72% and 41.19%, compared to the number without vaccination. When the durations of immunity were 90 and 120 days, the infection rates were 2.67 and 2.38. As the asymptomatic infection rate rose from 30% to 50%, the infection rate increased 0.92 (SD, 0.16) times. Conditioned on 70% adherence rate, with the same amount of limited available vaccines, the 20% and 40% vaccination coverage of one‐dose‐high‐coverage, the infection rates were 2.70 and 2.35; corresponding to the two‐doses‐low‐coverage with 10% and 20% vaccination coverage, the infection rates were 3.22 and 2.92. Our results indicated as the duration of immunity prolonged, the second wave of SARS‐CoV‐2 would be delayed and the scale would be declined. On average, the total infections in two‐doses‐low‐coverage was 1.48 times (SD, 0.24) as high as that in one‐dose‐high‐coverage. It is crucial to encourage people in order to improve vaccination coverage and establish immune barriers. Particularly when the supply is limited, a wiser strategy to prevent SARS‐CoV‐2 is equally distributing doses to the same number of individuals. Besides vaccination, NPIs are equally critical to the prevention of widespread of SARS‐CoV‐2.